A Portable Ultrasound System for Detecting Food Sweetness Based on Chewing Dynamics: A Preliminary Investigation - Zhan, Ye; Luo, Jingwen; Nandi, Souransu; Wang, Lidai; Singh, Tarunraj; Xia, Jun (Frontiers in Physics, 2020)
Type 1 diabetes (T1D) is an incurable disease that affects 1.25 million Americans. Diabetic patients typically rely on subcutaneous insulin infusions to regulate their glucose levels. A major contributor to their blood glucose levels is the amount of sugar intake, which cannot be easily tracked. While ultrasound imaging has been used to investigate the relationship between food characteristics and tongue movement, the technique utilized a bulky transducer array that cannot be translated into daily monitoring. Capitalizing on advanced electronics and data processing technologies, we developed a portable system that utilizes only a single ceramic disk to quantify the tongue movement in response to various levels of sweetness. After acquiring 32 subject datasets, we found a significant correlation between food sweetness and tongue movement. Our system can potentially be miniaturized into a wearable device for monitoring sugar intake, which will ultimately help T1D patients to better monitor and control their blood glucose levels and balance their diets accordingly.